Bourdieu and historical analysis. - Gorski, Philip S. (Politics, history, and culture., 2013)
The French sociologist Pierre Bourdieu had a broader theoretical agenda than is generally acknowledged. Introducing this innovative collection of essays, Philip S. Gorski argues that Bourdieu's reputation as a theorist of social reproduction is the misleading result of his work's initial reception among Anglophone readers, who focused primarily on his mid-career thought. A broader view of his entire body of work reveals Bourdieu as a theorist of social transformation as well. Gorski maintains that Bourdieu was initially engaged with the question of social transformation and that the question of historical change not only never disappeared from his view, but re-emerged with great force at the end of his career.